2019
DOI: 10.5535/arm.2019.43.5.535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Decreased Skeletal Muscle Index and Hand Grip Strength on Functional Recovery in Subacute Ambulatory Stroke Patients

Abstract: Objective To investigate the effect of decreased Skeletal Muscle Index (SMI) and hand grip strength on functional recovery in subacute ambulatory stroke patients. Methods Subacute stroke patients who were referred to the rehabilitation center were recruited. Decreased SMI and hand grip strength were diagnosed according to the Asian Working Group on Sarcopenia. Diagnostic criteria were decreased SMI and decreased unaffected hand grip strength. SMI was measured by bioelectrical impedance analysis. Unaffected han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
7
22
0
Order By: Relevance
“…HGS was indicated as a biomarker of recovery and prognostic of stroke [ 18 ]. Park indicated that decreasing of HGS had negative effects on functional recovery in subacute ambulatory stroke patients [ 17 ]. HGS was also found significantly associated with stroke mortality [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HGS was indicated as a biomarker of recovery and prognostic of stroke [ 18 ]. Park indicated that decreasing of HGS had negative effects on functional recovery in subacute ambulatory stroke patients [ 17 ]. HGS was also found significantly associated with stroke mortality [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…HGS is a useful biomarker to measure the recovery and prognostic after stroke [ 16 ], with decreased HGS forecasting worse survival and recovery after stroke [ 17 ]. The absence of measurable grip by one month after stroke indicates that there will be poor functional outcome [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 presents the PRISMA diagram for the study selection and reasons for exclusion. Three studies were conducted in Japan, [25][26][27] 2 in South Korea, 28,29 1 in Taiwan, 30 and 1 in the U.S. 24 Four included studies had a cross-sectional design, 24,25,29,30 and 3 were retrospective cohort studies. 26À28 Four studies included participants at <1 month since stroke onset 25À27,29 and 3 studies at >6 months since stroke onset.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…26À28 Four studies included participants at <1 month since stroke onset 25À27,29 and 3 studies at >6 months since stroke onset. 24,28,30 The Asian Working Group for Sarcopenia (AWGS) criteria was used to define sarcopenia in 3 studies, 25,26,29 whereas the European Working Group on Sarcopenia in Older People (EWGSOP) criteria was used in 2 studies. 27,28 The skeletal muscle index (SMI) or appendicular lean mass (ALM)/ height 2 by DXA or X-ray were used in 2 studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…At the stroke onset, low muscularity is associated with poor clinical outcomes [5]. Furthermore, after the stroke onset, muscle atrophy, called "stroke-induced sarcopenia," is associated with worse clinical outcomes, such as mortality and physical dysfunction [6]. Stroke-induced sarcopenia is observed in 42% of stroke survivors [7], and muscle loss is observed in the affected and unaffected limbs [8].…”
Section: Introductionmentioning
confidence: 99%